An Analysis of Indonesia Foreign Policy Under Jokowi’s Pro-People Diplomacy - Muhammad Tri Andika (Universitas Diponegoro, 2016)
Under Jokowi’s administration, Indonesia promotes “down to earth diplomacy” or also known as “pro-people diplomacy” by which he declared that Indonesia would focus on domestic affairs. It seems this policy will mostly be inward-looking paradigm compared with his predecessor, Susilo Bambang Yudhoyono, who emphasized strengthened role of Indonesia in the region with his “zero enemy and thousands friends”. The focus on domestic needs has raised concern from many observers on the less of Indonesia’s presence in international stages. But if we see the dynamic today, it seems not the case to underestimate Indonesia role in global stage. Against these background, the central question of this article is; how is pro-people diplomacy constructed and what challenges that are possessed? By adopting pro-people diplomacy Indonesia has received strong international concerns of Indonesia aggressive way in dealing with foreign issues. Does pro-people diplomacy has taken Indonesia to move away from its presence on international stages? This article emphasizes that while pro-people diplomacy has focus on domestic needs, but Indonesia’s engagement is even stronger.Keywords: Jokowi, Indonesia, foreign policy, pro-people diplomacy